2019
DOI: 10.1016/j.hpb.2019.03.103
|View full text |Cite
|
Sign up to set email alerts
|

Does the microbiology of bactibilia drive postoperative complications after pancreatoduodenectomy?

Abstract: positioning as potentially causative risk factors for VTE due to impaired lower extremity venous return. However, the influence of operative technique on VTE risk after DP is unknown. This study aims to examine the association between minimally invasive surgery (MIS) technique and the development of post-operative VTE after DP. Methods: Patients who underwent DP (2014e2015) were identified in the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) pancreas-specific database. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Enterococcus and Enterobacter species) with an increased risk for infectious complications, the clinical impact of these findings is questionable. 3, 7,14,36,42 For example, empirical antibiotic therapy is often not directed at Enterococcus species. 43,44 We found a complete concordance of bile and OSI cultures in only one of the nine patients with obtained OSI cultures and OSIs occurring within seven postoperative days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enterococcus and Enterobacter species) with an increased risk for infectious complications, the clinical impact of these findings is questionable. 3, 7,14,36,42 For example, empirical antibiotic therapy is often not directed at Enterococcus species. 43,44 We found a complete concordance of bile and OSI cultures in only one of the nine patients with obtained OSI cultures and OSIs occurring within seven postoperative days.…”
Section: Discussionmentioning
confidence: 99%
“…1,6,7,9,14,19,[31][32][33][34][35][36][37][38][39][40][41] The selected studies included one prospective and 16 retrospective cohort studies evaluating IOBCs obtained during pancreatoduodenectomy (supplemental material 3). Three studies reported detailed information about the microbiological assessment of IOBCs, 36,38,39 while the remaining 14 studies either did not report these methods or reported them as standard laboratory's procedures. Various definitions were used for wound infections, OSIs, abdominal infections and abscesses.…”
Section: Systematic Review Of Literature and Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…38 Maatman et al reported that enterococcus isolation from bile cultures in itself increased the risk of SSI. 39 Sugimachi et al reported a 41% correlation between biliary cultures and SSI cultures. 19 The evidence supporting the biliary microbiome as a major source of SSI after PD have led some to advocate for antibiotic selection based on preoperative biliary cultures.…”
Section: Discussionmentioning
confidence: 98%
“…In 89 pancreatic patients with positive bile cultures, Sourrouille et al reported that enterococcus was the most common isolated microorganism (48%) with 0% sensitivity to cefoxitin and 90% sensitivity to piperacillin-tazobactam 38 . Maatman et al reported that enterococcus isolation from bile cultures in itself increased the risk of SSI 39 . Sugimachi et al reported a 41% correlation between biliary cultures and SSI cultures 19 …”
Section: Discussionmentioning
confidence: 99%